Enchanted by the rodeo queen - Curtis, Melinda (Romance fiction writer) (Curtis, Melinda. Mountain Monroes, 2020)
She's looking for Mr. Right......but can he fill those boots? Former rodeo queen Emily Clark loves her life in Second Chance, Idaho, but she's through waiting for a cowboy to sweep her off her feet. Just as she's thinking of leaving town, she's offered a job by newcomer Jonah Monroe, a city slicker from Hollywood. Career-minded Jonah isn't looking to commit--to romance or a ranch--but Emily's determined to show him exactly what he's missing...